PERSEPSI MASYARAKAT TERHADAP AKHLAK REMAJA DI DESA PUTTADA KECAMATAN SENDANA KABUPATEN MAJENE - Mas'ud, Bulqia; Asrini; Fathani, Hamzah S. (PRODI PENDIDIKAN AGAMA ISLAM (PAI) SEKOLAH TINGGI AGAMA ISLAM NEGERI MAJENE, 2022)
The behavior of adolescents both in the city and in the village is quite concerning for the community. This study aims to find out the Puttada community's perception of the morals (akhlak) of adolescents in Puttada village. This study uses a qualitative research with a phenomenology research design. Data collection techniques in this study were observation, interviews, and documentation. The results of the study show that: 1) akhlak of adolescents towards oneself (commendable morals) are getting along well with people from various backgrounds, good cooperation with their peers, and honest. While despicable morals towards oneself such as playing until late at night, drinking intoxicating substances, and hooking up without boundaries; 2) akhlak of adolescents towards Allah SWT is portrayed by teenage boys who rarely conduct jumuah pray; 3) akhlak of adolescents towards the community are seen from mutual cooperation, helping others, and being polite to others; 4) akhlak of adolescents towards the environment are observed from their actions in maintaining the cleanliness of the village but they often show bad akhlak such as raising the sound of their motorcycle so that it interferes people’s peacefulness. For further research, the other researchers might reveal the causes of the decline in adolescent morals (akhlak), especially in villages.